SIMS measurement of magnesium isotopic ratios in Yamato-74191 and -75028 meteorites - Nishimura, Hiroshi; Okano, Jun (1982)
P(論文) Isotopic ratios of ^<24>(Mg)/^<25>(Mg) and ^<26>(Mg)/^<25>(Mg) have been measured for Mg-rich and A1-poor portions of matrix parts of the Yamato-74191 and -75028 meteorites with a Hitachi IMA 2A ion microprobe mass analyzer. Several terrestrial samples of lherzolites and a dunite were also analyzed. A clear evidence for the excess of ^<24>(Mg) has been found in the portions of Yamato-74191,where Mg/Si ratio is higher than 1.5 and Al/Mg ratio is less than 0.13. This excess ^<24>(Mg) can be evidence for the heterogeneity of the primordial solar nebula. departmental bulletin paper